The Geography of Community Supported Agriculture - Any Sulistyowati, Catharina; Afiff, Suraya; Baiquni, Muhammad; Siscawati, Mia (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Community Supported Agriculture (CSA) is considered an initiative that supports a more just and sustainable food system by creating a direct and mutual relationship between local farmers and consumers. Through an agreed mechanism, CSA supports farmers’ livelihoods as they have provided healthy food for consumers. This study contributes to the geographic mapping of CSA studies in Scopus-indexed social science journals and related articles. It traces the emergence and development of diverse CSA models, its political economy context, and the pattern of research themes across geographic areas. The findings reveal that the urban middle class in industrial countries can encourage farmers to produce healthy food and apply more sustainable farming systems. The findings also show that key factors of CSA emergence and development are the growing urban middle class with health, just, and environmental awareness; the availability of farmers who are willing to implement a more sustainable farming practice, and the platform or agreement that links them. The CSA practices across geographic areas differ as they are shaped by the political and economic context and the availability of opportunities. The limitation of this study is the lack of literature on CSA from non-western or non-industrialized countries. Therefore, this study suggests further research agenda on the following topics: exploration of CSAs in non-industrial and non-western countries; intangible value of CSA; diverse perspectives on CSA research; multidisciplinary research on CSA, processes and enabling conditions for CSA and CSA people; and potencies of CSA to solve in diverse social and environmental problems.